Does the number of free nicotine patches given to smokers calling a quitline influence quit rates: results from a quasi-experimental study - Mahoney Martin; Hyland Andrew; Celestino Paula; Fix Brian V; Cummings K Michael; Ossip Deborah J; Bauer Ursula (BMC, 2010)
Abstract Background The offer of free nicotine replacement therapy (NRT) can be a cost-effective marketing strategy to induce smokers to call a telephone quitline for quitting assistance. However, the most cost-effective supply of free NRT to provide to smokers who call a quitline remains unknown. This study tests the hypothesis that smokers who call a telephone quitline and are given more free nicotine patches would report higher quit rates upon follow-up 12 months later. Methods A quasi-experimental design was used to assess nicotine patch usage patterns and quit rates among five groups of smokers who called the New York State Smokers' Quitline (NYSSQL) between April 2003 and May 2006 and were mailed 2-, 4-, 6- or 8-week supplies of free nicotine patches. The study population included 2,442 adult (aged 18 years or older) current daily smokers of 10 or more cigarettes per day, who were willing to make a quit attempt, and reported no contraindications for using the nicotine patch. Outcome variables assessed included the percentage of smokers who reported that they had not smoked for at least 7-days at the time of a 12 months telephone follow-up survey, sustained quitting, delayed quitting and nicotine patch use. Results Quit rates measured at 12 months were higher for smokers in the groups who received either 2, 6, or 8 weeks of free patches. The lowest quit rate was observed among the group of Medicaid/uninsured smokers who were eligible to receive up to six weeks of free patches. The quit rate for the 4-week supply group did not differ significantly from the 6-week or 8-week groups. These patterns remained similar in an intent-to-treat analysis of 12-month quit rates and in an analysis of sustained quitting. Conclusion No clear cut dose response relationship was observed between the number of free nicotine patches sent to smokers and smoking outcomes. Baseline diferences in the characteristics of the groups compared could account for the null findings, and a more definitive randomized trial is warranted.